Pelatihan Penguasaan Soal UN Mata Pelajaran Bahasa Indonesia pada Siswa Kelas XII SMAN 2 Banjarmasin: Indonesian Language Subject Practice Mastery Training for Class XII Students of SMAN 2 Banjarmasin - Anwari, Muhammad Ridha; Istiqamah, Istiqamah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
This service aims to prepare students’ mental and academic abilities in facing national examination and to practice students to work on and answer the National Examination question’s material correctly. The method used in this service is in the form of lectures, discussions, question and answer, simulation of national examination questions, and evaluation. The subject in this service is SMAN 2 Banjarmasin’s students of XII grade which consists of 3 classes, namely XII Language programme, XII social programme 6, and XII Social programme 5, which have an average number of 30 students for each class. The results of this service show that SMAN 2 Banjarmasin’s students of XII grade get good grades in the national examination in Bahasa Indonesia’s subject simulation. The percentage 80% shows they have reached the passing grade and they passed. The rate 20% is still insufficient domain, and they need more practice in answering national examination questions